2020
DOI: 10.3738/1982.2278.3824
|View full text |Cite
|
Sign up to set email alerts
|

Análise Econômica Da Produção De Milho Doce Irrigado No Nordeste Do Mato Grosso Do Sul

Abstract: O objetivo deste trabalho foi avaliar os custos de produção e índices de lucratividade de diferentes tratamentos envolvendo lâminas de irrigação e épocas de cultivo, na cultura do milho doce irrigado, no nordeste de Mato Grosso do Sul. O trabalho foi conduzido na área experimental da Universidade Federal de Mato Grosso do Sul, campus de Chapadão do Sul, MS. O delineamento estatístico foi o de blocos casualizados, em esquema fatorial 4 x 2, constituído de quatro lâminas de irrigação (50, 75, 100, 125% da evapot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…For instance, Souza et al [12] estimated the Total Annual Operating Cost of irrigated sweet corn production in the northeast of Mato Grosso do Sul state, Brazil. The authors also evaluated several treatments involving irrigation plates and growing seasons, and their outcomes demonstrated that irrigated sweet corn was technically and economically viable for one year, with greater productivity during the summer/autumn season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Souza et al [12] estimated the Total Annual Operating Cost of irrigated sweet corn production in the northeast of Mato Grosso do Sul state, Brazil. The authors also evaluated several treatments involving irrigation plates and growing seasons, and their outcomes demonstrated that irrigated sweet corn was technically and economically viable for one year, with greater productivity during the summer/autumn season.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the literature have carried out economic feasibility studies on smaller-scale irrigated agricultural systems [9,12,14,15,20,28,29]. Most of them use traditional and deterministic economic methods to evaluate crops' viability.…”
Section: Methodsmentioning
confidence: 99%
“…Já os custos operacionais totais (COT) foram obtidos por meio do COE acrescentados das despesas gerais e o custo oportunidade (arrendamento). A estimativa de custos operacionais totais para análise econômica de baseados em resultados técnicos obtidos em experimentos tem sido utilizada por vários pesquisadores nos últimos anos (Kaneko et al, 2015;Souza et al, 2020).…”
Section: Custos De Produçãounclassified